Genetic testing and human leukocyte antigen in patients with hypertrophic cardiomyopathy and connective tissue diseases - Hiraya, Daigo; Murakoshi, Nobuyuki; Igarashi, Miyako; Xu, DongZhu; Ishizu, Tomoko (Frontiers in Genetics, 2024)
Hypertrophic cardiomyopathy (HCM) is caused by myocardial hypertrophy, often due to mutations in cardiac sarcomere protein genes such as beta-myosin heavy chain (MYH7) and myosinbinding protein C (MYBPC3). However, a significant proportion of HCM cases lack identified genetic mutations, and genotype-phenotype correlations remain unclear. Concurrently, potential associations between HCM and human leukocyte antigen (HLA) types, as well as connective tissue diseases, have been proposed. In this single-center study, we aimed to investigate the genetic and HLA profiles of patients with obstructive hypertrophic cardiomyopathy (HOCM) and connective tissue diseases, particularly focusing on the prevalence of genetic variants and HLA types. We conducted a detailed analysis of five patients with HOCM and connective tissue diseases and sarcoidosis, identifying rare variants in causative genes for HCM in two cases and observing specific HLA types that were relatively common. Notably, 15% of all HOCM cases presented with connective tissue diseases, mainly rheumatoid arthritis. These findings underscore the complexity of HCM etiology and suggest potential implications for both diagnostic strategies and therapeutic approaches in patients with concomitant inflammatory conditions.